How are we performing? Evidence for the value of science shows. Issue 1 (2nd January 2019) - Austin, Shanii R. P.; Sullivan, Miriam
ABSTRACT: Science performances, or science shows, combine scientific content with theatrical techniques for the purpose of engaging audiences with science. Despite the fragmented nature of the evidence on their effectiveness, science shows are commonly used in informal science learning, particularly in science centres, schools and museums. We have collated the literature into a comprehensive review of the history, typology and evidence base for science performance, drawing on a variety of literature including research discussing classroom demonstrations, science shows used in schools and museums, museum theatre and informal science learning. We found there is good qualitative and quantitative evidence to support the use of science shows both in informal science learning and as part of the school curriculum. Science shows that use demonstrations linked by a common theme have successfully produced both cognitive and affective outcomes, and theatrical science shows are frequently used to create awareness and stimulate discussion about complex and controversial science-related issues, such as HIV-AIDS and human cloning. The key features of structure, emotion and audience involvement that are present in good science shows make them a highly valuable and effective tool for both formal and informal science learning. Further research is needed to investigate the long-term impact of science performance.